Determination of electrokinetic potential of porous glasses by methods of streaming potential, electroosmosis and electrophoresis - Volkova, Anna; Ermakova, Ludmila; Volkova, Maria; Antropova, Tatyana V. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Complex research of structural and electrokinetic characteristics of nano- and the ultraporous glasses prepared from sodium borosilicate (SBG) glass DV1-Sh in KCl background solutions of various concentrations in a wide pH range has been performed. It is shown that for ultraporous membranes with the sizes of porous channels r in the range 10–70 nm appreciable electroosmotic flows and a good agreement of electrokinetic potential values determined by three different methods are observed. It is established that for nanoporous (r < 10 nm) glass membranes change of electroosmotic flow velocity with time is due to the development of concentration polarization.
Optica Applicata, Vol. 40, 2010, nr 2, s. 341-349
Keywords: optyka; electrokinetic potential; electroosmotic flow